Possibilities of food production on land with heavy metals - Vovk, Ana (Journal for Geography, 2023)
Heavy metals present in the soil are incorporated into plants and enter the food chain, causing serious diseases. It is necessary to choose an appropriate cultivation system, which depends on the geographical characteristics of the plot, such as the properties of the soil, bedrock or sediment, slope, exposure, wind direction, surface water runoff and radiation. The article presents an example of the use of flooded land with toxic sludge after floods using vertical systems. These are cultivation approaches where, by loading biomass, we raise the cultivation area and separate it from the base soil.  These approaches enable immediate food production in a safe manner, since the root systems of the plants are not in contact with the parent soil.
Keywords: Flood; soil; water; production system; heavy metals